Biochar derived from the spent coffee ground for ammonium adsorption from aqueous solution. (December 2021) - Nguyen, Van-Truc; Vo, Thi-Dieu-Hien; Tran, Thanh; Nguyen, Thanh-Nho; Le, Thi-Ngoc-Chau; Bui, Xuan-Thanh; Bach, Long-Giang
Abstract: Water sources are contaminated with nutrients such as nitrogen, which can cause eutrophication, resulting in degradation of the aquatic environment and severe effects on aquatic ecosystems. In this study, biochar derived from spent coffee grounds (CGB) was prepared and investigated for ammonium (NH4 + ) adsorption in water at different pH, NH4 + concentrations, and CGB dosage conditions. The most suitable conditions for NH4 + adsorption by CGB were found at pH of 7, initial NH4 + concentration of 40 mg L −1, and CGB dosage of 2 g L −1 . Data of NH4 + adsorption was highly compatible with the Langmuir isotherm with an R 2 of 0.976. Compared with biochars prepared from other agricultural by-products, CGB exhibited a high NH4 + adsorption capacity (Qmax  = 51.52 mg g −1 ). Pseudo-second-order model fitted well the adsorption data. The use of spent coffee grounds to prepare NH4 + adsorbent biochar not only saves the cost of solid waste treatment but also creates materials to adsorb pollutants in the water and is a source of additional nutrients for crops or soil improvement. Graphical abstract: Image 1 Highlights: Biochar from the coffee ground (CGB) showed great potential for NH4 + adsorption. Optimal condition for NH4 + adsorption was pH = 7, NH4 +  = 40 mg L −1, CGB = 2 g L −1 . NH4 + adsorption of the CGB well-fitted with the Langmuir isotherm with R 2 of 0.976. The CGB exhibited high NH4 + adsorption capacity with Qmax  = 51.52 mg g −1 . The NH4 + adsorption on the CGB followed the pseudo-second-order model.